2004
DOI: 10.1073/pnas.0308336100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a prostate cancer susceptibility locus on chromosome 7q11–21 in Jewish families

Abstract: Results from over a dozen prostate cancer susceptibility genomewide scans, encompassing some 1,500 hereditary prostate cancer families, indicate that prostate cancer is an extremely heterogeneous disease with multiple loci contributing to overall susceptibility. In an attempt to reduce locus heterogeneity, we performed a genomewide linkage scan for prostate cancer susceptibility genes with 36 Jewish families, which represent a stratification of hereditary prostate cancer families with potentially increased loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…CNVs in the region have previously been reported in control populations [57]. Chromosome 7q11-21 has previously been associated with cancer [58,59] and interestingly, both regions identified in the current study (7q11.21 and 16p11.2) have been found as CN gains in small bowel adenocarcinomas [60], which raises questions whether this is evidence in favour of the findings of the current study, or calls into question the stringency of the analysis which reported it.…”
Section: Discussionmentioning
confidence: 99%
“…CNVs in the region have previously been reported in control populations [57]. Chromosome 7q11-21 has previously been associated with cancer [58,59] and interestingly, both regions identified in the current study (7q11.21 and 16p11.2) have been found as CN gains in small bowel adenocarcinomas [60], which raises questions whether this is evidence in favour of the findings of the current study, or calls into question the stringency of the analysis which reported it.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] Since the post hoc analysis indicated a strong linkage signal with homogeneity among the Hasidic Jewish families, association mapping may be especially suitable in this population because of its limited number of founders. 38,39,46,47 Furthermore, one would expect enrichment for homozygous segments surrounding susceptibility genes among pVUR cases from this population. We did not detect regions of homozygosity within the chromosome 12 locus in the Hasidic Jewish patients, but this may be due to the lack of close consanguinity among families studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these three linkage regions, multiple chromosomal regions have been suggested to harbor PCa susceptibility genes from multiple genome-wide linkage analyses in PCa families ascertained in North America, Europe and Australia. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Notably, the International Consortium for Prostate Cancer Genetics (ICPCG) was formed in 1996 to coordinate efforts among investigators across the world for identifying PCa susceptibility genes. To date, more than 2000 families with at least two men affected with PCa have been recruited by members of ICPCG.…”
Section: Rare and High-penetrance Pca Susceptibility Genesmentioning
confidence: 99%